Is workplace spirituality associated with business ethics?. Issue 5 (13th July 2015) - Ayoun, Baker; Rowe, Louis; Yassine, Fatima
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to empirically explore the potential association between spirituality and business ethics in a hotel workplace. Design/methodology/approach – A scenario-based quantitative approach was used to collect data from 165 practicing professionals in the hotel industry. Findings – The results show that spirituality, as measured by the Spiritual Transcendence Scale (STS), did not correlate significantly with measures of ethical perception, ethical judgment, ethical intention or perceived moral intensity. There was, however, evidence to suggest that spirituality may be able to contribute incrementally to future research. Research limitations/implications – This study demonstrates that the dynamic associations between spirituality and ethics may produce different outcomes in different industry settings. Practical implications – If hotel companies focus on developing ethical standards, the effects on the business ethics of managers could be considerably greater than relying on the spirituality of managers or the encouragement of expression of spirituality in the workplace. Originality/value – Although the relationship between spirituality and ethics seems to be sensible, the empirical assessments on how managers' workplace spirituality relate to their business ethics is notably lacking. The present study sought to fill this gap in literature.